1953
DOI: 10.3181/00379727-83-20386
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Method for Determination of Hydroxyproline.

Abstract: During the course of investigations on the effects of thermal exposure upon rat skin and tail-tendon( 1), we had occasion to utilize the method of Neuman and Logan for the determination of hydroxyproline ( 2 ) as a measure of the collagen content ( 3 ) . In the application of this method considerable difficulty was experienced in obtaining reproducible, linear standard curves. Frequently, the standard curves would display the form of an exponential function, making the selection of suitable aliquots of an unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1957
1957
1977
1977

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…(5). Here an aliquot of each fraction was tested with the modified ninhydrin reagent (6) and the remaining portion analyzed for hydroxyproline with the aid of the procedure of Martin and Axelrod (7). BRIJ, thiodiglycol, and phenol, usually added to the eluting buffer, interfere with the color reaction and were, therefore, eliminated.…”
mentioning
confidence: 99%
“…(5). Here an aliquot of each fraction was tested with the modified ninhydrin reagent (6) and the remaining portion analyzed for hydroxyproline with the aid of the procedure of Martin and Axelrod (7). BRIJ, thiodiglycol, and phenol, usually added to the eluting buffer, interfere with the color reaction and were, therefore, eliminated.…”
mentioning
confidence: 99%
“…Analysis of the cleaned hydrolysates for hydroxyproline was carried out initially using the Martin and Axelrod modification (13) of the Neuman and Logan method (14). A with those given by the more complex method of Prockop and Udenfriend (12) usually revealed no significant differences.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen was estimated based on the content of hydroxyproline in the tissue by the method of Neuman and Logan (1950), according to the Martin and Axelrod (1953) modification for the determination of hydroxyproline. Tissue samples were collected from pools of 8 to 12 culture tubes by the method of Gerarde and Jones (1953).…”
Section: Methodsmentioning
confidence: 99%
“…There appears to be neither an enhancement nor retardation of growth at the levels used, nor is the gross morphology of the cells appreciably altered. While Mollendorf (1942Mollendorf ( , 1944 found a slight growth inhibition at an ascorbic acid level of 200 /~g./ml., it is likely that much higher concentrations are required to obtain marked effects. Hengstmann (1939) found that cell degeneration was marked at 2000 #g./ml., but Jeney and Toro (1937) routinely employed 1700 /zg./ml.…”
Section: Effect Of Excess Ascorbic Acid On Collagen Formation and Cellmentioning
confidence: 99%